Frequency and risk factors of musculoskeletal disorders in high risk occupation workers in Urban, Karachi - Muhammad Ovais; Shiraz Shaikh; Memon , Athar Hussain (Journal of the Pakistan Medical Association, 2022)
Objective: To determine the frequency and risk factors of musculoskeletal disorders in high-risk occupation workers in an urban setting. Method: The analytical cross-sectional study was conducted in Karachi from July to December 2020, and comprised office workers, operation theatre technicians and coolies. The presence of musculoskeletal disorders was assessed using the Nordic Musculoskeletal Questionnaire to determine factors associated with moderate to severe condition. Data was analysed using SPSS 20. Results: Of the 300 male subjects, 100(33.3%) each were office workers, operation theatre technicians and coolies. The overall mean age was 33.25±6.8 years (range: 18-50 years). The overall prevalence of musculoskeletal disorders was 179(59.7%). Besides, 117(65.4%) patients with musculoskeletal disorders had intermediate stage of the disease. The lower back and neck were the most common site of trouble involved in preceding 12 months 111(43.6%) each. Conclusion: Prevalence of musculoskeletal disorders was found to be a common problem affecting high-risk occupational workers. Key Words: High-risk occupations, Musculoskeletal disorders.